Absorption and emission of single attosecond light pulses in an autoionizing gaseous medium dressed by a time-delayed control field - Chu, Wei-Chun; Lin, C. D. (My University, 2013)
An extreme ultraviolet (EUV) single attosecond pulse passing through a laser-dressed dense gas is studied theoretically. The weak EUV pulse pumps the helium gas from the ground state to the 2s2p(1P) autoionizing state, which is coupled to the 2s2(1S) autoionizing state by a femtosecond infrared laser with the intensity in the order of 1012 W/cm2. The simulation shows how the transient absorption and emission of the EUV are modified by the coupling laser. A simple analytical expression for the atomic response derived for δ-function pulses reveals the strong modification of the Fano lineshape in the spectra, where these features are quite universal and remain valid for realistic pulse conditions. We further account for the propagation of pulses in the medium and show that the EUV signal at the atomic resonance can be enhanced in the gaseous medium by more than 50% for specifically adjusted laser parameters, and that this enhancement persists as the EUV propagates in the gaseous medium. Our result demonstrates the high-level control of nonlinear optical effects that are achievable with attosecond pulses.